Neuro Marketing-An Emerging Concept - Telang, V; Sharma, S; Panga, M; Dubey, A (International Journal of Computer Sciences and Engineering, 2025)
Modern management approaches are nowadays focusing more on human behavior. Whether it’s human Resource management, marketing management or advertisement and publicity the behavior and attitude of humans towards various aspects of life have been under a scanner. The purpose is to enhance both the productivity at operational level and marketability for sales revenue generation. Thus the combination of technology along with brain to study consumer behavior has gained immense importance today. Neuro Marketing can be hailed as one of the marketing innovations in today’s times. The research paper is related to exploring the finer nuances of neuro marketing, its relation to neuro science and its usage by companies to enhance their sales. Many companies are using the techniques and methods of neuro marketing to revise their earlier perception of consumers regarding their product with success. The study reveals that there is a lot of potential for neuro marketing to be used as tool for studying the buying behavior of an Indian middle class consumer.